2017
DOI: 10.1001/jamaneurol.2017.2545
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Infiltration in Primary Central Nervous System Lymphoma

Abstract: IMPORTANCEVisual impairment in primary central nervous system lymphoma (PCNSL) is caused mostly by intraocular lymphomatous involvement (vitritis and retinal infiltration), whereas optic nerve infiltration (ONI) is a rare condition.OBJECTIVE To describe the clinical presentation of ONI, its imaging characteristics, and outcome. DESIGN, SETTING AND PARTICIPANTSA total of 752 patients diagnosed with PCNSL were retrospectively identified from the databases of 3 French hospitals from January 1, 1998, through Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Recent studies have concentrated on isolated PIOL (8,9), concluding that it is a less aggressive form of the disease (10,11). However, to the best of our knowledge, only a few studies to date have focused on IOL with CNS involvement or following intracerebral mass due to the difficulty of diagnosis and rarity of the disease (12,13). As a result, questions concerning the biological behavior of IOL remain unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have concentrated on isolated PIOL (8,9), concluding that it is a less aggressive form of the disease (10,11). However, to the best of our knowledge, only a few studies to date have focused on IOL with CNS involvement or following intracerebral mass due to the difficulty of diagnosis and rarity of the disease (12,13). As a result, questions concerning the biological behavior of IOL remain unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast enhancement was seen in MRI in most optic nerve lymphoma patients. According to Ahle et al (24), MRI showed contrast enhancement of the optic nerve in all seven optic nerve infiltrated patients described. In our review, enhanced MRI was observed in 19 of the 22 cases.…”
Section: Discussionmentioning
confidence: 87%
“…Ahle et al described optic nerve infiltration in 7 patients from a 752-PCNSL cohort; MRI showed optic nerve thickening in only three of the seven cases. However, the authors considered that standard MRI findings without sequences focused on the optic nerves might be interpreted as usual, and that orbital MRI focusing on both optic nerves and including high-resolution fat-suppressed sequences might increase the chance of detecting optic nerve enlargement (24). Optic nerve lymphoma usually manifests as massive nerve swelling (2, 18) and could last for a long time without treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential diagnosis for this patient, who presented with sudden onset right eye vision loss, is broad. Important diagnoses to consider include optic neuropathy, optic neuritis, autoimmune disorders, inflammatory pseudotumors, and other compressive neuropathies, including optic nerve glioma, optic nerve meningioma, optic nerve or orbital metastases, inherited disorder, and toxic, nutritional, or metabolic optic neuropathies [7]. Urgent ophthalmology consult may be necessary in order to influence the differential, ordering of subsequent testing, and prevention of further progression of the disease.…”
Section: Discussionmentioning
confidence: 99%